2004
DOI: 10.1021/ja045678j
|View full text |Cite
|
Sign up to set email alerts
|

Dioxygen Activation at a Single Copper Site:  Structure, Bonding, and Mechanism of Formation of 1:1 Cu−O2 Adducts

Abstract: To evaluate the fundamental process of O(2) activation at a single copper site that occurs in biological and catalytic systems, a detailed study of O(2) binding to Cu(I) complexes of beta-diketiminate ligands L (L(1) = backbone Me; L(2) = backbone tBu) by X-ray crystallography, X-ray absorption spectroscopy (XAS), cryogenic stopped-flow kinetics, and theoretical calculations was performed. Using synchrotron radiation, an X-ray diffraction data set for L(2)CuO(2) was acquired, which led to structural parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
200
1
3

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 190 publications
(222 citation statements)
references
References 76 publications
18
200
1
3
Order By: Relevance
“…The prediction of a singlet ground state is consistent with experiment. The large difference in relative energetics between CASPT2 and DFT, with the former providing agreement with experiment for the correct ground state while the latter fails to do so, is consistent with past experience regarding Cu-O 2 adducts [28,29]. Analysis of the results for 9 suggests that deficiencies in basis-set and active-space size may lead to errors as large as 4-5 kcal mol À1 in predicted relative energies for 7; however, the qualitative ordering of the relative energies noted before are invariant to errors of this magnitude.…”
supporting
confidence: 85%
See 2 more Smart Citations
“…The prediction of a singlet ground state is consistent with experiment. The large difference in relative energetics between CASPT2 and DFT, with the former providing agreement with experiment for the correct ground state while the latter fails to do so, is consistent with past experience regarding Cu-O 2 adducts [28,29]. Analysis of the results for 9 suggests that deficiencies in basis-set and active-space size may lead to errors as large as 4-5 kcal mol À1 in predicted relative energies for 7; however, the qualitative ordering of the relative energies noted before are invariant to errors of this magnitude.…”
supporting
confidence: 85%
“…On the basis of computed relative energies and all of the frequency data, Schatz et al concluded that the coordination mode was end-on. However, interpretation of density functional results in such systems can be complicated by the varying degrees of multiconfigurational character that 1:1 Cu-O 2 adducts may exhibit both intrinsically and as a function of coordination motif [27][28][29]. This variation can lead to significant errors in computed energies and, in principle, vibrational force constants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In both of these cases, the resulting compounds with a variety of ligands can have singlet ground states that exhibit substantial biradical character because of the spin separation associated either with two d 9 Cu͑II͒ ions or one such ion and a superoxide radical anion. [40][41][42][43][44][45][46][47][48][49][50][51][52] Wave function theories restricted to a single determinant are poorly suited to the description of such species since singlet biradicals are intrinsically two determinantal. 53,54 Moreover, even when oxidation states more likely to be characterized as closed shell in nature are considered, e.g., ͓LCu͑III͔͒ 2 ͓O͑2−͔͒ 2 , computational studies have found that large contributions from dynamical correlation effects influence relative isomer energetics.…”
Section: Application To Supported Cuo 2 and Cu 2 O 2 Systemsmentioning
confidence: 99%
“…47,92 There is, however, no alternative to using DFT for geometry optimizations and it has always been considered that using restricted DFT and even using unrestricted DFT would provide useable geometries for the systems investigated here or their analogs. 35,57,93,94 We will take advantage of the appealing possibility of SF-DFT to optimize such adducts. In order to explore this point, we here have considered the ͓Cu͑tren͒͑O 2 ͔͒ + adduct in its two possible coordination modes, end-on and side-on.…”
Section: Application: Geometry Optimizationsmentioning
confidence: 99%